The mechanical behavior of single crystal and polycrystalline pure magnesium. (December 2021) - Kang, Minju; Dixit, Neha; Hazeli, Kavan; Xie, Kelvin; Hemker, Kevin; Ramesh, K.T.
Abstract: We present a simplified constitutive model, based on the dominant deformation mechanisms, to capture the mechanical behavior of magnesium. This approach takes into account (1) the accumulation and annihilation of 〈 a 〉 and 〈 c + a 〉 dislocations, (2) the volume fraction of extension twins, and (3) two material domains — the parent region and the twinned region. We first show that the model successfully captures the material responses of single crystal magnesium under different loading conditions. We then extend the model for application to a polycrystalline magnesium alloy. The results provide a simple and straightforward approximate model for magnesium and its alloys under various loading conditions. Highlights: A simplified constitutive model is developed capturing the anisotropic behavior of Mg. The model is calibrated with experimental data of single crystal magnesium. The model captures the material responses of both single crystal and polycrystalline. The parameters and the simplicity of this approach lend to fast-running simulations.